Manufacturing flow batteries using advanced 3D printing technology—A review - Wu, Ji; Xu, Shaowen (Frontiers in Chemical Engineering, 2023)
In the past decade, electrochemical energy storage systems such as rechargeable batteries have been explored as potential candidates for the large-scale storage of intermittent power sources. Among these, redox flow batteries stand out due to their low fabrication costs, high scalability, and long cycle life. Several redox flow battery pilot plants with MWh capacity have been constructed worldwide, although their commercial profitability is currently under investigation. 3D printing as a burgeoning technology offers unlimited opportunities in the process of optimizing the design, performance, and fabrication cost of redox flow batteries as compared to traditional top-down manufacturing techniques. This review discusses the principles of various redox flow batteries and 3D printing techniques, followed by explaining the advantages, disadvantages, and major factors to consider when using 3D printing in the construction of efficient redox flow batteries. The practical applications of 3D printing for redox flow batteries with different redox chemistries in the past decade are critically summarized, including classical all-vanadium, Zn/Br, and novel competitors. Lastly, a summary is provided along with outlooks that may provide valuable guidance for scientists interested in this research frontier.